Young lives : Perú round 2 survey - Escobal D'Angelo, Javier; Ames, Patricia; Cueto, Santiago; Penny, Mary; Flores, Eva (University of Oxford, 2017)
"This report presents initial findings from the second round of data collection in Peru between late 2006 and early 2007. It provides a broad outline of key child poverty indicators, as well as changes that have taken place since the first round of research in 2002."–Abstract.